Pendidikan Karakter Siswa Sekolah Dasar Kelas Rendah melalui Pembelajaran Menyanyikan Lagu Anak-Anak - Dahlan Dahlan (Action Research Journal, 2022)
This article aims to describe; (1) Character Education (2) Characteristics of Low Grade Elementary School Students (3) Learning to Sing Children's Songs. This research uses descriptive research method. Character education is very important to be taught in educational institutions, especially at the elementary school level. Sources of data in this study were students in grades I – III SDN Kutosari, Karanganyar District, Pekalongan Regency. Collecting data using non-test techniques such as recording, taking notes, and observing. The data analysis technique used qualitative data analysis techniques. The results of this study indicate that learning to sing children's songs can be used as a character building for elementary school students in grades I – III SDN Kutosari.